ASSESSMENT OF A POSSIBLE DECREASE IN THE EFFICIENCY OF THE SHIP OPERATING WITHIN A YEAR - Вишневская, Ольга (SWorldJournal, 2020)
The planning of the ship operating should be carried out taking into account the possible deviations in the predicted operating conditions, parameters of the production process, and, as a result, efficiency. The paper deals with the problem of the taking